Pluralism in American Music Education Research Essays and Narratives (Landscapes: the Arts, Aesthetics, and Education, 2018)
This volume examines pluralism in light of recent music education research history and pluralistic approaches in practice. Pluralistic research holds the potential to blend frameworks, foundations, methods, and analysis protocols, and leads to a sophisticated understanding of music teaching and learning. This blending could take place in a range of contexts that may span an individual study to a lifelong research agenda. Additionally, pluralistic ideals would guide the addressing of questions as a community. The volume also illuminates the work of innovative music education researchers who are constructing pluralistic research studies and agendas, and advocate for the music education profession to embrace such an approach in order to advance shared research goals. The ramifications of this transformation in music education research are a subject of discussion, including the implications for researcher education and the challenges inherent in conducting and disseminating such research.